Meta Analisis Korelasi Kemampuan Adaptabilitas dan Kepuasan Karir - Pratama, Daniel Yoga; Yudiarso, Ananta (Fakultas Psikologi Universitas YARSI, 2023)
This study discussed the meta-analysis of 17 literature studies that examined the relationship between career adaptability (CA) and career satisfaction (CS). Career satisfaction is a person's feeling of satisfaction that has achieved. Career adaptability is a person's ability to adapt to the environment, tasks, and work stress. The total number of participants in these 17 literature studies was 10,596. The analysis found career adaptability and career satisfaction had a medium to large effect size correlation of r = 0.422 (95% CI 0.351 - 0.493). The moderator variable of a continent variable where the study was conducted included, the effect size correlation yielded 0.3957 (95% CI -0.178 – 0.207). The continent represents the cultural diversity across the 17 studies conducted in various countries. The analysis involved the type of measuring instrument short/long-form found effect size correlation 0.4704 (95% CI -0.070 – 0.023). The Moderator variables did not affect the relationship between the two variables. This study has no publication bias with an Egger's Regression value of 0.902. The Moderator variables did not affect the relationship between the two variables. This study has no publication bias with an Egger's Regression value of 0.902. The significant implications in this meta-analysis emphasize the importance of replicating research on the direct relationship between career adaptability and career satisfaction. Replicating the study is crucial to enhance the external validity of the relationships between both variables.